2013
DOI: 10.1080/16506073.2013.819376
|View full text |Cite
|
Sign up to set email alerts
|

Safety Behaviour Enhances the Acceptability of Exposure

Abstract: Compulsive washing and contamination fears are among the most common symptoms of obsessive-compulsive disorder (OCD). Research suggests that exposure and response prevention (ERP) is effective for OCD. However, ERP is prone to dropouts and refusals, and a substantial proportion of clients therefore do not receive the care they need. A proposed solution involves the judicious use of safety behaviour to enhance the acceptability of exposure-based interventions. The current study aimed to test this proposed solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 38 publications
4
21
1
Order By: Relevance
“…As with other research into the acceptability of CBT interventions for OCD and anxiety, this study's findings support the notion that a cognitive framework and focus on approach-supporting behaviour increases the perceived ability to adhere to an intervention's requirements (e.g. Levy and Radomsky, 2014;Milosevic and Radomsky, 2013;Rachman et al, 2008;Senn and Radomsky, 2015;Sighvatsson and Salkovskis, 2013). Given that the case studies of reducing accommodation suggest that negative reactions may be a barrier to treatment adherence, identifying alternatives that allow the intervention to become more acceptable, such as guiding significant others to provide adaptive support, is an important step towards ensuring that those who would benefit from the intervention are willing to complete it.…”
Section: Discussionsupporting
confidence: 84%
“…As with other research into the acceptability of CBT interventions for OCD and anxiety, this study's findings support the notion that a cognitive framework and focus on approach-supporting behaviour increases the perceived ability to adhere to an intervention's requirements (e.g. Levy and Radomsky, 2014;Milosevic and Radomsky, 2013;Rachman et al, 2008;Senn and Radomsky, 2015;Sighvatsson and Salkovskis, 2013). Given that the case studies of reducing accommodation suggest that negative reactions may be a barrier to treatment adherence, identifying alternatives that allow the intervention to become more acceptable, such as guiding significant others to provide adaptive support, is an important step towards ensuring that those who would benefit from the intervention are willing to complete it.…”
Section: Discussionsupporting
confidence: 84%
“…Overall, prior mental health treatment and anxiety (but not depressive) symptoms were associated with lower acceptability and anticipated adherence ratings. Consistent with Rachman and colleagues (2008) and recent experimental research (Levy & Radomsky, 2014), the findings from this study support the notion that safety behavior enhances the acceptability of CBT for anxiety disorders. Coupled with recent literature on the efficacy of exposure with safety behavior Hood et al, 2010;Milosevic & Radomsky, 2008, 2013aRachman et al, 2011;van den Hout et al, 2011), overall it appears that safety behavior may not interfere with exposure and may actually promote treatment engagement and success.…”
Section: Table 3 Comparison Of Medication-savvy and Medication-naivesupporting
confidence: 91%
“…In fact, there could be situations in which the presence of a safety aid may actually assist in obtaining threatrelevant information. Indeed, previous research has shown that safety behavior enhances behavioral approach to anxiety-provoking stimuli during exposure (Hood et al, 2010;Levy & Radomsky, 2014;Milosevic & Radomsky, 2008, 2013a. By contrast, extinction-based CBT emphasizes complete engagement with feared stimuli to promote habituation, and the presence of safety aids (even when used judiciously) may be perceived as interfering with this process.…”
Section: Table 3 Comparison Of Medication-savvy and Medication-naivementioning
confidence: 84%
See 1 more Smart Citation
“…permitting SBs as needed, and gradually diminishing these behaviours over time) may reduce anxiety during exposure, increase treatment acceptability, and thus decrease attrition rates (e.g. Levy and Radomsky, 2014;van den Hout et al, 2011).…”
Section: Safety Behaviour During Exposure: Helpful or Hindering?mentioning
confidence: 99%